Menentukan Kelipatan Persekutuan Terkecil (KPK) dan Faktor Persekutuan Terbesar (FPB) dengan Menggunakan Metode PEBI - Suci Yuniati (Beta: Jurnal Tadris Matematika, 2012)
Mathematics is a tool to develop ways of thinking, because mathematics is indispensable for both daily life and progressing science and technology so that mathematics needs to be taught to each student since elementary school, even since kindergarten. Establishing a thorough understanding of math requires a priorly love of math. Therefore a teacher should be able to create "Fun Learning" in the classroom. Fun learning in mathematics can be created when a teacher is able to teach math concepts using methods and techniques variedly so that it is not menoton and boring for students. One material that is taught at elementary and junior high is lesson of KPK and FPB and it is also widely used to understand the concept of high school math. There are several techniques that are commonly used in instilling the concept of KPK and FPB that is using the concept of factors and multiplication. But the concept is not enough. There, it needs for the addition of new concepts that need to introduce to students so that students have many alternatives in resolving issues concerning the KPK and FPB. Given the importance of these concepts, the author tries to connect to other concepts in determining KPK and FPB that is an unusual method introduced in textbooks in school. This method consists of four techniques in solving KPK and FPB. This method is obtained by combining several mathematical concepts to be applied in determining KPK and FPB. Four such techniques determine KPK and FPB in the form of fractions, using the Euclidean algorithm, a concept of prime numbers, and slices in the concept of set theory. The four methods are not prevalent but be expected to be an alternative for teachers so that they can add insight into mathematical concepts entirety.